Avaliação da influência dos impulsionadores para superação das barreiras da manufatura sustentável: survey nas indústrias têxteis brasileiras de acabamento - Leite, Roberto Rodrigues (2019)
Industrial manufacturing generates results that cause many questions, because, without concern for the environment, economic development is compromised, as well as the benefits to society. It is important to find alternatives for improvement, both economic and social, that do not harm the environment. Industries are seen as major polluters and to improve this scenario, sustainable manufacturing management can contribute to reducing impacts to the environment. Sustainable manufacturing is part of debates that include social, environmental and economic issues, to promote the conscious and more efficient use of raw materials and inputs, preserving natural resources and minimizing waste generation, thereby reducing environmental impacts, promoting benefits economic and social. In order to implant a sustainable manufacturing in the industrial processes it is important to know the impact factors of this implantation. This work identified in the literature the main barriers and drivers that impact the implementation of sustainable manufacturing, with the main objective of evaluating the level of influence that the drivers can exert on the barriers to its overcoming. Through the information obtained, a research instrument was developed that was submitted to the evaluation of specialists in the textile area, making possible the elaboration of a questionnaire for conducting a survey. With the answers obtained in the survey, it was possible to correlate the two factors, drivers and barriers, resulting in the identification of the level of influence that the drivers have on the barriers to the implantation of sustainable manufacturing in the Brazilian textile finishing industry. Although models of analysis of impellers and barriers of sustainable manufacturing have been presented in recent years, they do not establish the degree of influence that a booster exerts on a barrier to its overcoming in the Brazilian textile industry, especially in the wet finish sector. Through the work, it was possible to conclude that the impellers exercise different degrees of influence in the overcoming of certain barriers, information that serves as support in the decision process of the managers for the implantation of the sustainable manufacture in the Brazilian textile industry.